The periplasmic binding protein NrtT affects xantham gum production and pathogenesis in Xanthomonas citri. Issue 10 (13th September 2017) - Sampaio, Aline; Pegos, Vanessa Rodrigues; Oshiro, Elisa Emiko; Balan, Andrea
Abstract : In Xanthomonas citri, the bacterium that causes citrus canker, three ATP‐binding cassette (ABC) transporters are known to be dedicated to the uptake of sulfur compounds. In this work, using functional, biophysical and structural methods, we showed that NrtT, a periplasmic component of the ABC transporter NrtCB, is an alkanesulfonate‐binding protein and that the deletion of the nrtT gene affected xantham gum synthesis, adhesion and biofilm production, similarly to the phenotype obtained in the X. citri ssuA ‐knockout strain, in which the alkanesulfonate‐binding protein SsuA is absent. Although NrtA and SsuA share similar ligands, the function of these proteins is not complementary. These results emphasize that organic‐sulfur sources are directly involved with bacterial infection in vivo and are needed for pathogenesis in X. citri . Abstract : NrtT is a periplasmic‐binding protein from an ATP‐binding cassette transporter present in Xanthomonas citri, the bacterium that caused citrus canker. NrtT showed similarities with other organic sulfur‐binding proteins and its structure was altered in the presence of the alkanesulfonate MOPS. The deletion of X. citri nrtT affected the production of xantham gum, adhesion, biofilm formation and citrus canker symptoms, supporting the involvement of alkanesulfonates and sulfate in pathogenesis.